A luminescence-based method to assess antigen presentation and antigen-specific T cell responses for in vitro screening of immunomodulatory checkpoints and therapeutics - Álvarez Freile, Jimena; Qi, Yuzhu; Jacob, Lisa; Lobo, Maria Franceskin; Lourens, Harm Jan; Huls, Gerwin; Bremer, Edwin (Frontiers in Immunology, 2023)
Investigations into the strength of antigen-specific responses in vitro is becoming increasingly relevant for decision making in early-phase research of novel immunotherapeutic approaches, including adoptive cell but also immune checkpoint inhibitor (ICI)-based therapies. In the latter, antigen-specific rapid and high throughput tools to investigate MHC/antigen-specific T cell receptor (TCR) activation haven't been implemented yet. Here, we present a simple and rapid luminescence-based approach using the human papillomavirus 16 (HPV16) E711-20 peptide as model antigen and E7-TCR transgenic Jurkat.NFAT-luciferase reporter cells. Upon E7 peptide pulsing of HLA-A2 + cell lines and macrophages, an effector to target ratio dependent increase in luminescence compared to non-pulsed cells was observed after co-incubation with E7-TCR expressing Jurkat, but not with parental cells. Analogous experiments with cells expressing full-length HPV16 identified that E7-specific activation of Jurkat cells enabled detection of endogenous antigen processing and MHC-I presentation. As proof of concept, overexpression of established checkpoints/inhibitory molecules (e.g., PD-L1 or HLA-G) significantly reduced the E7-specific TCR-induced luminescence, an effect that could be restored after treatment with corresponding targeting antagonistic antibodies. Altogether, the luminescence-based method described here represents an alternative approach for the rapid evaluation of MHCdependent antigen-specific T cell responses in vitro. It can be used as a rapid tool to evaluate the impact of the immunosuppressive tumor microenvironment or novel ICI in triggering effective T cell responses, as well as speeding up the development of novel therapeutics within the immune-oncology field.